KOMUNIKASI ANTARPRIBADI WARGA BELAJAR DI PKBM SARI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Riza, Rangga Ofa; Natuna, Daeng Ayub; Bahar, Aswandi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This study aims to determine Interpersonal communication PKBM citizens studying in Sari. The problem of this research is interpersonal communication How high PKBM citizens studying in the coastal city fringe districts sari pekanbaru.The benefits of research to increase knowledge on matters relating to the Communication, Interpersonal communication, Citizens Learning, especially for researchers. This research will benefit all citizens of learning. This is a descriptive study with a quantitative approach that aims to describe the results of research by the numbers. Mechanical sampling using simple random sampling (random sampling). Data collection techniques in this research is to use the questionnaire as a method of data collection, totaling 45 items statement. After the questionnaire in the trial, there are 8 items that are not valid. Data obtained from respondents who were 30 to sample the test and 45 people with Cronbach's alpha = 0.941. Based on Table 4.11, it can be explained that the level of interpersonal communication learners Based on the analysis of data with the highest percentage is the average of 88.24%, while the percentage of moderate to an average of 8.23% and a low percentage is the average of 3, 12%. The average score of the mean and standard deviation of each indicator is very high it can be seen from the indicators Disclosure mean values obtained were 4.28 and 0.73 SD is at a very high interpretation. then in view of the indicator obtained Empathy mean values of 4.39 and 0.70 SD which is at a very high interpretation. Onwards of indicator Support in learning obtained mean values of 4.17 and 0.86 SD which is at a very high interpretation. Judging from the indicators Positive Feelings obtained mean values SD of 43.98 and 0.98 which are in high interpretation. Furthermore, in view dati indicator of similarity obtained mean values of 4.28 and 0.75 SD which is at a very high interpretation. Having done the research and data processing can be concluded that the learners have high levels of interpersonal communication is very high.Keywords: Communication, Interpersonal Communications, Citizens Learning.